The Effectiveness Analysis of Student Creativity Increasing Program Using Grimm’s Rainbow Media - Misbahul Munir; Hamzah Hamzah; Lukmanul Hakim; Iwan Henri Kusnadi; Magdalena Magdalena (Departement of Mathematics Education, 2023)
Because everyone is born with the capacity to be creative and because this potential may be cultivated and nourished, creativity is a skill that everyone possesses to varying degrees. This study focused on kids aged five to six whose creative faculties had not yet fully matured and who had not used the appropriate medium in their learning activities. This study sought to ascertain how imaginatively kids between the ages of five and six used Grimm's rainbow media. The A-B-A design is utilized in this study's (SSR) approach. Both observation and instrument evaluation were used as data gathering methods in this investigation. The data is collected as percentage values, which are then processed using descriptive statistical methods, visual data analysis, and condition-specific data analysis. According to the study's findings, including Grimm's Rainbow media in learning activities might enhance kids' creative thinking skills when they are between the ages of five and six. The study's findings and conclusion indicate that Grimm's Rainbow media can boost young children's creativity